Targeted violence against law enforcement officers. (14th November 2016) - Schouten, Ronald; Brennan, Douglas V.
Abstract : As highly visible representatives and guardians of society, law enforcement officers (LEOs) are very public figures. Injury or death in the line of duty, whether due to accidents or intentional acts of violence, is an occupational hazard for LEOs. Targeted assaults on police officers, referred to as ambushes in previous literature, are a particularly perplexing problem with significant implications for society at large. In the summer of 2016, the latest in a series of high‐profile acts of violence aimed at police occurred, leading to increased examination of the acts themselves and their causes. This article examines recent trends in assaults on LEOs, focusing on predatory rather than reactive attacks, and applies a threat assessment model to a case of targeted violence against police. We use State of Washington v. Christopher Monfort (2015), a prosecution for arson, assault with intent to murder, and murder, as a case example, to examine how the threat assessment model, and the concepts of affective versus predatory violence help in understanding targeted violence against LEOs, assessing its risk, and managing it. Copyright © 2016 John Wiley & Sons, Ltd.